Indoor Air Quality measurement in server and battery rooms in ICT Companies in Macedonia - Koteli, Nikola; Ivanova, Maja; Mitreski, Kosta (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
In this paper we will analyze the results from the Indoor Air Quality measurements in the server and battery rooms in ICT companies. The measurements were done on request of the ICT companies after installation of air-quality filters, after having problems with failure of hard disks. The monitoring equipment is the compact multi gas air quality system (airpointer® by recordum). It is able to measure PM10, CO, O3, SO2, NO/NO2/NOX, RH and temperature with its standard reference method sensors over a wide range of concentration. The measurements were performed every day, 24 hours a day in Data-center and Battery rooms. These gases alone or in combination with humidity and/or with temperature reacts with copper and silver in electronic circuit boards, server cards, cooling equipment, datacom connections resulting in micro - electronic corrosion/malfunction resulting in downtime losses. Downtime which translates into data loss, revenue loss and ultimately customer dissatisfaction.
Keywords: indoor air quality, airpointer, monitoring system